Raising of Microvascular Flaps : a Systematic Approach. - Wolff, Klaus-Dietrich (Springer International Publishing, 2017)
This operative manual offers high-quality photographs showing cadaver preparations alongside explanatory colour drawings. It is designed to enhance understanding of the anatomy through 3D perspectives and by showing structures that are hidden in preparation.